Salicylic Acid Is Needed in Hypersensitive Cell Death in Soybean but Does Not Act as a Catalase Inhibitor. - Tenhaken, R. (1997)
The function of salicylic acid (SA) in hypersensitive cell death was studied in a soybean (Glycine max)-Pseudomonas syringae pv glycinea system. The infection of cell cultures with bacteria leads to a hypersensitive reaction (HR), which is dependent on an appropriate avirulence gene and on low concentrations of SA. The requirement for SA is essential for a process shortly before the onset of the HR-caused cell death 5 to 6 h after infection with bacteria. SA given 10 to 12 h after infection or preincubation cannot rescue the completion of the cell death program. SA does not inhibit catalase or ascorbate peroxidase in soybean. In addition, the in vivo capacity of the cell culture for the rapid metabolism of H2O2 is not altered by SA. This clearly shows that SA is needed for the HR-caused cell death for a reaction downstream of the oxidative burst. Lipid peroxides accumulate during the HR, but the loss of membrane control precedes the generation of lipid peroxides. The accumulation of lipid peroxides in the HR can be prevented by lipid antioxidants. Nevertheless, cell death kinetics remain unaltered in the presence of antioxidants. It is concluded that lipid peroxides are a consequence of cell death, but not the primary cause of it.